(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the surgical outcomes of mandibular third molar (MTM) removal with Parant II impaction using the vertical tooth sectioning technique assisted by a 45° angled handpiece. Methods: A prospective interventional clinical study was conducted on 95 patients treated at Bach Mai Hospital and Hai Phong University of Medicine and Pharmacy Hospital, employing a pre- and post-intervention design without a control group. Results: The mean surgical duration was 25.3 ± 7.1 minutes; patients over 25 years of age required significantly longer procedures (28.0 minutes) compared to those aged 16–25 years (23.0 minutes) (p = 0.01). Pain, swelling, and trismus peaked at 48 hours postoperatively and markedly subsided after 7 days. The complication rate was low, including infection (5.3%), postoperative bleeding (3.2%), and transient neurosensory disturbance (1.1%), despite 40% of the teeth being in proximity to the inferior alveolar canal. Overall outcomes were classified as Good in 67%, Fair in 24%, and Poor in 9% of cases. Predictors of poorer outcomes included age > 25 years (aOR = 1.9), history of pericoronitis (aOR = 2.4), impaction depth C (aOR = 3.8), and prolonged surgical duration (aOR = 1.25). Conclusion: The vertical tooth sectioning technique using a 45° angled handpiece is a safe and effective approach for Parant II mandibular third molar extractions, providing good postoperative recovery and minimizing complications, particularly inferior alveolar nerve injury.